Nordic LifeWatch cooperation, final report: A joint initiative from Denmark, Iceland, Finland, Norway and Sweden - Hanssen, Frank Ole; Heggberget, Tor Gravråk; Bladt, Jesper; Endresen, Dag Terje Filip; Forsius, Martin; Gudmundsson, Gudmundur A.; Gärdenfors, Ulf; Heiðmarsson, Starri; Kindvall, Oscar; Koch, Wouter; Koivula, Hanna; Laiho, Eija-Leena; et al. (NordForsk, 2016)
The main goal of the present report is to outline the possibilities for an enhanced cooperation between the Nordic countries within eScience and biodiversity. LifeWatch is one of several ESFRI projects which aim to establish eInfrastructures and databases in the field of biodiversity and ecosystem research. Similarities between Nordic countries are extensive in relation to a number of biodiversity related issues. Most species in Nordic countries are common, and frequently the same challenges concerning biodiversity and ecosystem services are addressed in the different countries. The present report has been developed by establishing a Nordic LifeWatch network with delegates from each of the Nordic countries. The report has been written jointly by the delegates, and the work was organized by establishing working groups with the following themes: strategic issues, technical development, legal framework and communication. Written during two workshops, Skype meetings and emailing, the following main issues are discussed in the present report: * Scientific needs for improved access to biodiversity data and advanced eScience research infrastructure in the Nordic countries. * Future challenges and priorities facing the international biodiversity research community. * Scientific potential of openly accessible biodiversity and environmental data for individual researchers and institutions. * Spin-off effects of open access for the general public. * Internationally standardized Nordic metadata inventory. * Legal framework and challenges associated with environmental-, climate-, and biodiversity data sharing, communication, training and scientific needs. * Finally, some strategic steps towards realizing a Nordic LifeWatch construction and operational phase are discussed. Easy access to open data on biodiversity and the environment is crucial for many researchers and research institutions, as well as environmental administration. Easy access to data from different fields of science creates an environment for new scientific ...